PTU-118 Endoluminal vacuum therapy for the management of boerhaave syndrome. Issue 2 (June 2019) - Stevens, Sophie; Thomas, Robert; Peters, Christopher; Moorthy, Krishna; Hanna, George; Direkze, Natalie; Hoare, Jonathan
Abstract : Introduction: Boerhaave syndrome is associated with high morbidity and mortality rates. Outcomes are dependent on early recognition and intervention. Until recently, surgery has been the mainstay of management. However, with recent advances in therapeutic endoscopy, there has been increasing interest in endoscopic options, including endoluminal vacuum therapy (EVT). EVT is a minimally invasive technique, allowing wound debridement and drainage; promoting granulation tissue formation to enable wound healing. EVT has been associated with excellent clinical outcomes, including lower mortality rates when compared to both surgery and oesophageal stenting. EVT has been adopted into practice across Europe for the management of oesophageal perforations. However, in the UK there have only been two cases reported. We report a case of a 66 year old female with Boerhaave syndrome, successfully managed with EVT. Methods: EVT for oesophageal perforation involves the placement of a polyurethane sponge into the wound cavity. The cavity is initially assessed with an endoscope before an overtube is introduced under visual control. The sponge is pushed into the cavity through the overtube. Once the sponge is in place, the overtube is removed; allowing the sponge to unfold. Sponge position is confirmed endoscopically and adjusted if necessary. The sponge is connected via a trans-nasal drain to continuous negative pressure. Sponge exchange is performed every 3–5 days. Results: Having been deemed unfit for surgical intervention, due to difficulties with ventilation and haemodynamic instability, our patient was initially stabilised on the Intensive Care Unit (ICU) with the aid of radiologically placed chest drains and intravenous antibiotics. She was subsequently referred for EVT, using the EsoSPONGE ® (B.Braun, Medical Ltd, Sheffield, UK). Her first therapeutic endoscopy took place on Day 10 of admission; revealing a 5 cm defect in the oesophageal wall and an adjacent cavity; major vessels and the chest drains could be visualised endoscopically. The EsoSPONGE was placed into the cavity and connected to suction. She remained on ICU for 3 months and during this period her EsoSPONGE was exchanged 16 times; resulting in resolution of sepsis and healing of the defect. She was successfully stepped down from ICU and has now been discharged. Conclusions: EVT was an effective management strategy for our patient with Boerhaave syndrome. Use of the EsoSPONGE aided drainage of the septic focus and closure of the defect; with this our patient made an excellent recovery. Mortality for this case would otherwise have been extremely high as she was too unstable for surgery. This case supports the evidence that EVT provides a promising approach for the management of Boerhaave syndrome.